System Usability Scale (SUS) Aplikasi Android Pemeriksaan Persyaratan Teknis Kendaraan Bermotor - Fadia Qatrunada; Siti Shofiah; Rizal Aprianto (Pusat Riset dan Inovasi Nasional, 2024)
In testing motorized vehicles as an effort to open up information systems, namely by sending the results of testing vehicle specifications and storing a database of vehicle test results and if possible analyzing the results. However, the test results record can only explain the reasons for rejection, there are no pictures or recommendations for repairs as well as information on component damage based on technical requirements orally to the vehicle owner. Therefore, it is necessary to innovate the use of Android applications. Researchers used the System Usability Scale (SUS) test on the application to validate the technical requirements and determine its effectiveness on 20 respondents. Research and Development (R&D) methodology, Waterfall method with pre-use Blackbox testing to see if the results work properly. Verification results of vehicle requirements have been successfully carried out, including photos taken during inspection. If you enter the reason for the refusal, the data will be validated and the final results of filling out the application will be printed. The System Usability (SUS) scale is 80.75 acceptable, the grade level is category B, the adjective rating is in the excellent category. This means that the application can improve the vehicle specifications inspection service.